MUSEUM BUDAYA DENGAN KONSEP LANSEKAP ISLAM DI SINJAI - Rudianto, Rudianto; Rahayu, Irma (Nature: National Academic Journal of Architecture, 2015)
Sinjai city contains the historical values that support the existence of the museum. Application of landscape design of the building and its environment can improve the quality and human’s comfort. The purpose of this writing is introducing to the public about the richness of culture which is manifested in the design concept of the Islamic landscape and facilitate the activities of the museum . Islam landscape architecture is an art that has a primary function to create the beauty of the surrounding environment where human life with the increasing of the urban comfort, easiness, and health.